Is Our Food Safe from Pesticides? - Frederick M. Fishel (EDIS)
PI230, a 5-page illustrated fact sheet by Frederick M. Fishel, describes the integrated pest management practices followed by growers of our food supply, how tolerances for pesticides in foods are determined by the EPA, and how annual testing of commodity samples for pesticides is conducted. Published by the UF Department of Agronomy, June 2010.